Diabetes Enhances Vulnerability to Particulate Air Pollution–Associated Impairment in Vascular Reactivity and Endothelial Function - O’Neill, Marie S.; Veves, Aristidis; Zanobetti, Antonella; Sarnat, Jeremy A.; Gold, Diane R.; Economides, Panayiotis A.; Horton, Edward S.; Schwartz, Joel (Circulation (New York, N.Y.), 2005)
Background— Epidemiological studies suggest that people with diabetes are vulnerable to cardiovascular health effects associated with exposure to particle air pollution. Endothelial and vascular function is impaired in diabetes and may be related to increased cardiovascular risk. We examined whether endothelium-dependent and -independent vascular reactivity was associated with particle exposure in individuals with and without diabetes. Methods and Results— Study subjects were 270 greater-Boston residents. We measured 24-hour average ambient levels of air pollution (fine particles [PM 2.5 ], particle number, black carbon, and sulfates [SO 4 2− ]) ≈500 m from the patient examination site. Pollutant concentrations were evaluated for associations with vascular reactivity. Linear regressions were fit to the percent change in brachial artery diameter (flow mediated and nitroglycerin mediated), with the particulate pollutant index, apparent temperature, season, age, race, sex, smoking history, and body mass index as predictors. Models were fit to all subjects and then stratified by diagnosed diabetes versus at risk for diabetes. Six-day moving averages of all 4 particle metrics were associated with decreased vascular reactivity among patients with diabetes but not those at risk. Interquartile range increases in SO 4 2− were associated with decreased flow-mediated (−10.7%; 95% CI, −17.3 to −3.5) and nitroglycerin-mediated (−5.4%; 95% CI, −10.5 to −0.1) vascular reactivity among those with diabetes. Black carbon increases were associated with decreased flow-mediated vascular reactivity (−12.6%; 95% CI, −21.7 to −2.4), and PM 2.5 was associated with nitroglycerin-mediated reactivity (−7.6%; 95% CI, −12.8 to −2.1). Effects were stronger in type II than type I diabetes. Conclusions— Diabetes confers vulnerability to particles associated with coal-burning power plants and traffic.